OPTIMALISASI PERAN BANK SAMPAH SEBAGAI UPAYA MENINGKATKAN LITERASI DIGITAL DAN LITERASI LINGKUNGAN MASYARAKAT DESA SAGULING KABUPATEN CIAMIS - Lia Yulisma; Feri Bakhtiar Rinaldi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2023)
The implementation of the waste bank is social engineering to encourage people to sort waste. Through waste banks, an innovative solution was finally found to "force" people to sort waste. By equating waste with money or valuables that can be saved, people are finally educated to appreciate waste according to its type and value so that they are willing to sort waste. Implementation of 3R (reduce, reuse and recycle) in waste management at the source at the community. The "Tumras" Waste Bank is a Waste Bank located in Sagulingkolot , Rt/Rw 003/006 Saguling, Baregbeg, Ciamis. The formation of the Tumras Waste Bank and its management was approved by the Decree of the Head of  Saguling Number 147/Kpts.22/2019 on 30 July 2019. The existence of a Waste Bank can have a social impact, economic impact, and environmental impact. Problems related to waste management at the Waste Bank include social aspects, technical aspects, management aspects and institutional aspects. There are several strategy options based on this study, namely using technology as a medium for managing waste banks (digital literacy), holding regular meetings between managers and customers, communicating with the entire community to register as customers.